2019
DOI: 10.1186/s12887-019-1709-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of -multidrug-resistant Enterobacteriaceae in a neonatal unit in Johannesburg, South Africa

Abstract: Background Multi-drug resistant organisms are an increasingly important cause of neonatal sepsis. Aim This study aimed to review neonatal sepsis caused by multi-drug resistant Enterobacteriaceae (MDRE) in neonates in Johannesburg, South Africa. Methods This was a cross sectional retrospective review of MDRE in neonates admitted to a tertiary neonatal unit between 1 January 2013 and 31 December 2015. Results There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
74
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 25 publications
12
74
4
Order By: Relevance
“…Bacteria belonging to Enterobacterales, such as Escherichia coli, Klebsiella pneumoniae, Enterobacter, Citrobacter, Serratia, Proteus, and Morganella, often cause nosocomial infections. 1,2 During the last decade, the emergence of carbapenem-resistant Enterobacteriaceae (CRE), which led to limited treatment options, has become the main cause of clinical anti-infective treatment failure. 3,4 It is worth noting that carbapenem-resistant Enterobacter cloacae (CR-ECL), which is one of the most common species that has been focused on in studies of a single species of Enterobacterales, 5 has been reported in many countries such as Korea, the United States, India, and China.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria belonging to Enterobacterales, such as Escherichia coli, Klebsiella pneumoniae, Enterobacter, Citrobacter, Serratia, Proteus, and Morganella, often cause nosocomial infections. 1,2 During the last decade, the emergence of carbapenem-resistant Enterobacteriaceae (CRE), which led to limited treatment options, has become the main cause of clinical anti-infective treatment failure. 3,4 It is worth noting that carbapenem-resistant Enterobacter cloacae (CR-ECL), which is one of the most common species that has been focused on in studies of a single species of Enterobacterales, 5 has been reported in many countries such as Korea, the United States, India, and China.…”
Section: Introductionmentioning
confidence: 99%
“…Despite NICU admission and maximal organ support, neonates with proven BSI experienced high crude mortality rates (27%), comparable to that reported from other African country cohorts with similar proportions of preterm neonates. 20,21,30,31 Notably, most patients with proven BSI demised soon after blood culture collection (BSI-attributable mortality), highlighting the rapid clinical progression of bacteraemia, particularly in preterm neonates. Infection due to a Gram-negative pathogen was the single most important factor predicting neonatal mortality on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…17 In some African neonatal units, carbapenem-resistant Acinetobacter baumannii and Enterobacterales (CRE) are now leading causes of neonatal infectious deaths, especially in preterm infants. [18][19][20][21] In this paper we characterise the epidemiology of clinically suspected and laboratory-con rmed bloodstream infections at a large academic neonatal unit in South Africa, with analysis of factors associated with mortality in proven infections.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality and morbidity rates due to healthcareassociated infections (HAIs) are high in neonates who require intensive care because of their low immunity. In South Africa, the mortality from neonatal sepsis due to multi-drug resistant Enterobacteriaceae was reported to be 33.3% [1].…”
Section: Introductionmentioning
confidence: 99%